Polarisation insensitive wavelength de‐multiplexer using arrayed waveguide grating and polarisation rotator/splitter. Issue 8 (1st April 2019) - Onawa, Y.; Okayama, H.; Shimura, D.; Takahashi, H.; Yaegashi, H.; Sasaki, H.
Abstract : The authors report the polarisation insensitive operation of an arrayed waveguide grating using a polarisation rotator/splitter (PRS) waveguide device which attains identical wavelength characteristics and optical losses for both transverse electric (TE) and transverse magnetic (TM) polarisations. The proposed PRS device is composed of a rib structure waveguide and an asymmetrical directional coupler (ADC). The rib waveguide converts TM fundamental mode to TE first‐order mode. The ADC splits TE first‐order mode into the TE fundamental mode propagating in the sub‐adjacent waveguide. Experimental results confirm that the proposed device operates independently of light polarisations; channel isolation is nearly 20 dB, and no transmission wavelength shift or polarisation dependent loss are observed between TE and TM polarisations.